Viscoelastic properties and physicochemical characteristics of pressurized ostrich-meat emulsions containing gum additives - Utaiwan Chattong (2018)
© 2015 Elsevier Ltd. Minced-ostrich meat was blended and chopped with various proportions of gum powder in terms of carboxymethyl cellulose (CMC), locust bean gum (LBG) and xanthan gum (XAN) and other ingredients such as sodium chloride, sodium tripolyphosphate, linseed oil and ice. The mixed batters were then pressurized at 600 MPa and 50 °C for 40 min. Subsequently, their viscoelastic and physicochemical properties were assessed in terms of their dynamic oscillatory moduli, their resultant creep behavior, water-holding capacity and electrophoretic profiles. The results showed that the addition of individual gums and composite gum mixtures influenced both viscoelastic behavior and water-holding capacity of resulting pressurized ostrich-meat emulsions. The most elastic system (greatest G′ or smallest J 0 with 4.21 × 10 - 5 1/Pa) was the meat emulsion with 1% LBG added, while the least were those formed by adding 1% XAN or 0.5% XAN plus 0.5% CMC (J 0 with 10 × 10 - 5 and 20.3 × 10 - 5 1/Pa, respectively). Subsequent electrophoritic profiles and the measurement of the water-holding capacity of the materials suggested an evidence of ionic interaction between the basic ostrich-meat protein matrix and XAN or XAN plus CMC. Industrial relevance Ostrich meat emulsions containing composite gums were set by combined pressure and temperature. Subsequently, the pressurized gels were characterized by dynamic oscillatory, creep and other physicochemical measurements. In particular, the viscoelastic measuring system is a promising tool for ensuring quality of food biopolymers. Therefore, this methodology is relevant in the area of controlling quality or developing new products where difficulty exists in solubilising the samples.